Enhanced chondrocyte culture and growth on biologically inspired nanofibrous cell culture dishes - Bhardwaj G (Dove Medical Press, 2016)
Garima Bhardwaj,1 Thomas J Webster1,2 1Department of Chemical Engineering, Northeastern University, Boston, MA, USA; 2Center of Excellence for Advanced Materials Research, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: Chondral and osteochondral defects affect a large number of people in which treatment options are currently limited. Due to its ability to mimic the natural nanofibrous structure of cartilage, this current in vitro study aimed at introducing a new scaffold, called XanoMatrix™, for cartilage regeneration. In addition, this same scaffold is introduced here as a new substrate onto which to study chondrocyte functions. Current studies on chondrocyte functions are limited due to nonbiologically inspired cell culture substrates. With its polyethylene terephthalate and cellulose acetate composition, good mechanical properties and nanofibrous structure resembling an extracellular matrix, XanoMatrix offers an ideal surface for chondrocyte growth and proliferation. This current study demonstrated that the XanoMatrix scaffolds promote chondrocyte growth and proliferation as compared with the Corning and Falcon surfaces normally used for chondrocyte cell culture. The XanoMatrix scaffolds also have greater hydrophobicity, three-dimensional surface area, and greater tensile strength, making them ideal candidates for alternative treatment options for chondral and osteochondral defects as well as cell culture substrates to study chondrocyte functions. Keywords: chondrocytes, XanoMatrix™, cell culture, substrates, biomimetic scaffolds